SENIOR HIGH SCHOOL ENGLISH TEACHERS’ PUNCTUALITY, ATTENDANCE AND STUDENTS’ ACADEMIC PERFORMANCE - Maulana, Saima; ALIMAN, BAI DONNA; ULANGKAYA, ZAIDA (Advances in Social Sciences Research Journal, 2021)
This study sought to determine the Senior High School English teachers’ teaching practices in terms of punctuality, attendance and its relationship to students’ academic performance. Specifically, it determined the Senior High School English Teachers’ level of punctuality and attendance; the Senior High School Students’ level of academic performance in English; and the significant relationships of the teachers’ level of punctuality and attendance and their Senior High students’ level of performance in English. The study used the descriptive-correlational survey method. The respondents of the study were the twenty four (24) teachers of the twelve (12) senior high schools of Maguindanao, Philippines. There were two (2) Senior High English teachers that were chosen randomly from each senior high schools of Maguindanao. It has a total of twenty-four (24) Senior High English Teachers. In every teacher, there are 10 senior high school students chosen randomly with a total of two hundred forty (240) senior high school students. The immediate supervisors of the teachers from the twelve (12) secondary schools answered the research problem number 1, while the final grades in English of the two hundred forty (240) senior high students were taken from their English teachers to answer the research problem number 2. The respondents of this study were chosen randomly using lottery. Pearson’s Product - Moment Correlation Coefficient was used to determine the significant relationship of the level of punctuality and attendance of the English teachers to the students’ level of academic performance. Based on the findings of the study, it is concluded that the Senior High School English Teachers’ level of teaching practices is influenced by their punctuality and attendance. It further concluded that teachers’ punctuality and attendance contributed to students’ level of academic performance in English. Keywords: Senior High School English Teachers, Punctuality, Attendance, Students’ Academic Performance